MODEL PENGELOLAAN DANA DESA BERBASIS GOOD GOVERNANCE STUDI KASUS NAGARI LAREH NAN PANJANG SELATAN - Meidona, Syofria; Wahyuni EDT, Risa; Hendri, Novi; Yusman, Ali (Universitas Sumatera Barat, 2024)
This study analyzes the process of managing village funds in Nagari Lareh Nan Panjang Selatan, Padang Pariaman Regency, using the principles of accountability, transparency, and community participation to realize good governance. The analysis method used is included in qualitative descriptive research. Primary data is obtained through direct interviews with informants in related fields such as the village head, village secretary, BUMNag director and village officials around Nagari Lareh Nan Panjang. The results showed that Nagari Lareh Nan Panjang Selatan has implemented village fund management in accordance with applicable regulations, by prioritizing the principles of accountability, transparency, and community participation, which contribute to the achievement of good governance. This research provides insight into effective village fund management practices, in line with applicable regulations and can be said to be accountable, transparent and uphold community participation. The principle of accountability in the planning, implementation and accountability process of Village Fund Management in Nagari Lareh Nan Panjang Selatan is in accordance with Permendagri No. 113 of 2014. Good management will realize good government as well. The application of this accountability principle aims as a benchmark or reference for the government in carrying out activities in village financial management. The results of this study also participate in other regency.